Linguistic Methodical Foundations of Teaching Allusions in Foreign Literature - Aminovna, Bozorova Matlyuba (International Journal on Integrated Education, 2024)
The article "Linguistic Methodical Foundations of Teaching Allusions in Foreign Literature" explores the pedagogical approaches and linguistic principles involved in teaching allusions from foreign literature. The author delves into the significance of allusions as literary devices and their role in enhancing language comprehension and cultural understanding. Through a comprehensive analysis, the article highlights the importance of integrating allusions into foreign language teaching methodologies to foster critical thinking skills and deepen students' appreciation of literary works. The study offers valuable insights into effective strategies for incorporating allusions into language instruction, emphasizing the need for a nuanced understanding of both linguistic and literary elements. The article describes methods for analyzing allusions expressed in the works of foreign writers in high school literature classes, in particular, when teaching Homer’s epic “Iliad”.